1996
DOI: 10.1007/bf02509719
|View full text |Cite
|
Sign up to set email alerts
|

Macro‐ and microlevel factors related to sense of community: The case of temporary neighborhoods in Israel

Abstract: This study examines macro and micro factors influencing the development of sense of community (Davidson & Cotter, 1980) in two different populations (immigrants and veterans) in new temporary neighborhoods in Israel. At the macrolevel, the major factors examined were population size, population density, number of dwelling units in the site, urbanity of the area, ethnic heterogeneity, and peripheriality of the region. Three kinds of variables were examined on the microlevel: (a) personal attitudes: evaluation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
1
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 36 publications
(49 reference statements)
0
27
1
3
Order By: Relevance
“…Based on these considerations, we hypothesized that ethnic composition of the territory per se is not able to threaten sense of community. Two studies, carried out respectively in Israel (Sagy, Stern, & Krakover, 1996) and the United States (Brodsky, O'Campo, & Aronson, 1999) also revealed that sense of community is not related to ethnic heterogeneity of the community.…”
Section: Is Sense Of Community Influenced By a Population's Ethnic Comentioning
confidence: 92%
“…Based on these considerations, we hypothesized that ethnic composition of the territory per se is not able to threaten sense of community. Two studies, carried out respectively in Israel (Sagy, Stern, & Krakover, 1996) and the United States (Brodsky, O'Campo, & Aronson, 1999) also revealed that sense of community is not related to ethnic heterogeneity of the community.…”
Section: Is Sense Of Community Influenced By a Population's Ethnic Comentioning
confidence: 92%
“…In a conceptual framework of community psychology the notion of community identity and the PSOC are closely related to each other and so are the two research fields. Much of the literature on the PSOC has focused on communities that were territorially defined, and on particular neighbourhoods and block groups (Brodsky, O'Campo, & Aronson, 1999;Perkins, Floris, Rich, Wandersman, & Chavis, 1990;Unger & Wandersman, 1985), housing complexes (Sagy, Stern, & Krakover, 1996), towns and cities (Buckner, 1988;Glynn, 1981Glynn, , 1986). More recently, PSOC has also been investigated in relational communities (Pretty, 1990;Pretty, Andrewes, & Collett, 1994;Royal & Rossi, 1996) and organizational settings (Burroughs & Eby, 1998;Fyson, 1999).…”
Section: Community Identity In a Functionalist Perspectivementioning
confidence: 99%
“…Research on the predictors of neighborhood sense of community has focused to a large extent on individual-level predictors of the individual-level sense of community (e.g., Davidson, Cotter, & Stovall, 1991) with a few exceptions (e.g., Sagy, Stern, & Krakover, 1996;Sampson, Raudenbush, & Earls, 1997). Buckner (1988), however, suggests that future research focus on determining the extent to which sense of community is influenced by environmental as well as individual variables to determine the degree to which sense of community can be influenced by system-level variables (Buckner, 1988).…”
Section: Correlates Of Neighborhood-level Sense Of Communitymentioning
confidence: 99%